PREVENTION AND TREATMENT OF PAIN SYNDROMES IS AN IMPORTANT TREND IN MODERN MEDICINE - V. H. Timerbaev (Неотложная медицинская помощь)
Prevention and treatment of pain syndromes is an important trend in modern medicine.